Drying aji panca in a solar photovoltaic dryer of heat pipe - Palo Tejada, Juan (2020)
In this work, tests were carried out on the drying of the ají panca in a forced air solar dryer using fifteen vacuum tubes (Heat pipe), a closed cabin where the product is placed and a squirrel cage turbine that is fed by a system of two photovoltaic panels of 50 W each. The heated air is driven by the turbine from the vacuum tubes to the product in the cabin, in this work the unidimensional Fick difusion equation and numerical methods were used to determine the mass transfer coefficient 2.61 x 10- 9 ms-1 and the effective diffusivity coefficient 1.52 x 10-10 m2 s-1 and it was concluded that the drying temperature of is 55 °C is the one that best fits the results estimated by the model. The solar vacuum tube dryer is capable of maintaining an operating temperature between 50 °C to 55 °C for an irradiance of 450 to 1100 W /m2 between 9:30 am and 2:30 pm, under these conditions, in two days it is possible to dry the ají panca up to 8% moisture content. Traditional drying of this product takes between seven and ten days.